GOVERNANCE OF PUBLIC SERVICE COMPLAINT HANDLING THROUGH THE JABAR SABER HOAKS - Aisha Kamilah Manliati; Ivan Darmawan; Jovanscha Qisty Adinda (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
Public service complaints are an important instrument in realizing transparent, participatory, and accountable governance. This study aims to analyze the governance of public service complaints through the Jabar Saber Hoax website as a communication medium between the community and the West Java Provincial Government. The research method used was qualitative descriptive with data collection techniques in the form of observation, interviews, and documentation during the internship at the Jabar Saber Hoax Unit. The result of the study show that the Jabar Saber Hoax website supporting transparency, public participation, and accurate information delivery through a digital-based complaint system. In its implementation, there are still several obstacles, such as limitation of people’s digital literacy, delays in responding to complaints, and limited supporting features on the website. Therefore, it is necessary to strengthen the complaint management system, increase human resources and develop more inclusive and resnponsive features to increase the effectiveness of public service complaint and strengthen public trust in digital-based government services. this study highlights the importance of integrating inter-agency coordination and adopting adaptive governance approaches to ensure faster and more effective complaint resolution. The utilization of data analytics and feedback mechanisms can also enhance decision-making processes and improve service quality continuously. In addition, strengthening public outreach and digital education programs is crucial to ensure that all segments of society can access and utilize the platform effectively.